Descriptions of four kleptoparasitic spiders of the genus Mysmenopsis (Araneae, Mysmenidae) and their potential host spider species in the genus Linothele (Araneae, Dipluridae) from Ecuador - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2015)
Four new species of the genus Mysmenopsis are described: M. onorei n. sp., M. otonga n. sp., M. fernandoi n. sp. and M. chiquita n. sp. All species were collected in diplurid webs and are therefore assumed to be kleptoparasitic. Five potential host species of the genus Linothele (Dipluridae) that were collected with the symbionts are also described: Linothele yanachanka n. sp., L. pukachumpi n. sp., L. zaia n. sp., L. tsachilas n. sp. and L. quori n. sp.